Unique physicochemical properties and rare reducing sugar trehalulose mandate new international regulation for stingless bee honey - Zawawi, Norhasnida (Elsevier BV, 2022)
Stingless bee honey (SBH) of four stingless bee species (Heterotrigona itama, Geniotrigona thoracica, Tetragonula carbonaria, and Tetragonula hockingsi) from two geographic regions (Malaysia and Australia, n = 36) were studied for their physicochemical parameters, including total phenolic and multi-elemental contents. Sugar analysis confirmed the prominent presence of trehalulose in all samples. All SBH failed to meet the CODEX Standard for honey moisture, free acidity, and total fructose plus glucose levels. One-way ANOVA, principal component analysis (PCA) and hierarchical component analysis (HCA) confirm distinctive differences between Australian and Malaysian SBH with Australian SBH having significantly (P < 0.05) higher pH, total phenolic, total mineral, and electrical conductivity attributes. Toxic elements in all SBH were much lower than standard CODEX limit. The species G. thoracica produced honey with significantly (P < 0.05) higher trehalulose than both Australian bee species. This research will add value to SBH and hasten new international standards ensuring commercial viability, safety, quality, and marketability of SBH.